2017
DOI: 10.1111/hsc.12476
|View full text |Cite
|
Sign up to set email alerts
|

Social work-generated evidence in traumatic brain injury from 1975 to 2014: A systematic scoping review

Abstract: The International Network for Social Workers in Acquired Brain Injury (INSWABI) commissioned a systematic scoping review to ascertain the social work-generated evidence base on people with traumatic brain injury (TBI) of working age. The review aimed to identify the output, impact and quality of publications authored by social workers on this topic. Study quality was evaluated through assessment frameworks drawn from the United Kingdom National Service Framework for Long-Term Conditions. In the 40-year period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…The impact of a TBI can result in a domino effect of changes not just for the patient, but for their family members as well (Mantell et al, 2018). The associated deficits in day-to-day functioning can also lead to a breakdown of the family system as roles begin to shift to accommodate to the patient’s condition (Carlozzi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of a TBI can result in a domino effect of changes not just for the patient, but for their family members as well (Mantell et al, 2018). The associated deficits in day-to-day functioning can also lead to a breakdown of the family system as roles begin to shift to accommodate to the patient’s condition (Carlozzi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the findings highlight the complexity of DoLS and the practical difficulties of making reliable judgements of capacity for people with brain injuries. Whilst referring to social work practice with people with ABI but possibly more widely applicable, Mantell et al (2018) suggested the difficulty of using structured assessments to apply abstract criteria to determine real world decisionmaking. Arising from this is the possibility of inherent variability in capacity assessment because the very concept of capacity is a somewhat imprecise notion rather than a fixed entity.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of knowledge of ABI, especially that of the invisible impact of the condition, was noted to be a significant issue, as found in previous research (George and Gilbert, 2018). Social work practice in particular is criticised by the survey respondents, and ABI is not noted to feature highly in research by the academic branch of the profession (Mantell et al, 2017). Criticisms of practice and the harm caused by a lack of knowledge of the impact of ABI upon functioning are longstanding and would seem to remain unaddressed (Acquired Brain Injury and Mental Capacity Act Interest Group, 2014;Flynn, 2016;House of Lords, 2014;Morgan, 2017;Norman, 2016;Summerfield, 2011).…”
Section: Discussionmentioning
confidence: 99%